Challenges and solutions for physical testing in sport: the profiling physical qualities tool - Till, K.; Collins, N.; McCormack, S.; Owen, C.; Weaving, D.; Jones, B. (Strength and Conditioning Journal, 2023)
The measurement, analysis, and reporting of physical qualities within sport is vital for practitioners to support athlete development. However, several challenges exist to support this process (e.g., establishing comparative data, managing large data sets) within sport. This article presents 7 challenges associated with physical testing in sport and offers solutions to overcome them. These solutions are supported by a description of the Profiling Physical Qualities (ProPQ) tool. The ProPQ tool uses advanced data analysis, visualization, and interactive elements, to enhance stakeholders' use of data to optimize player development and coaching practices. The ProPQ is currently used across rugby league in England.